Exogenous Gamma-Aminobutyric Acid Application Induced Modulations in the Performance of Aromatic Rice Under Lead Toxicity - Ashraf, Umair; Mahmood, Sammina; Anjum, Shakeel Ahmad; Abbas, Rana Nadeem; Rasul, Fahd; Iqbal, Javed; Mo, Zhaowen; Tang, Xiangru (Frontiers in Plant Science, 2022)
Gamma-aminobutyric acid (GABA) is a non-protein amino acid and has a multi-functional role in abiotic stress tolerance. A pot experiment was conducted to assess the role of exogenous gamma-aminobutyric acid (GABA) application to modulate the growth, yield, and related physio-biochemical mechanisms in two aromatic rice cultivars i.e., Guixiangzhan (GXZ) and Nongxiang 18 (NX-18) under Pb toxic and normal conditions. The experimental treatments were comprised of Ck: without Pb and GABA (control), GABA: 1 mM GABA is applied under normal conditions (without Pb), Pb+GABA: 1 mM GABA is applied under Pb toxicity (800 mg kg-1 of soil), Pb= only Pb (800 mg kg-1 of soil) is applied (no GABA). The required concentrations of GABA were applied as foliar spray. Results revealed that Pb stress induced oxidative damage in terms of enhanced malondialdehyde (MDA), electrolyte leakage (EL), and H2O2 contents while exogenous GABA application improved leaf chlorophyll, proline, protein and GABA contents, photosynthesis and gas exchange, and antioxidant defense under Pb toxicity in both rice cultivars. Moreover, glutamine synthetase (GS) and nitrate reductase (NR) activities were variably affected due to GABA application under Pb stress. The yield and related traits i.e., productive tillers/pot, grains/panicle, filled grain %, 1000-grain weight, and grain yield were 13.64 and 10.29, 0.37% and 2.26%, 3.89 and 19.06%, 7.35 and 12.84%, and 17.92 and 40.56 lower under Pb treatment than Pb+GABA for GXZ and NX-18, respectively. Furthermore, exogenous GABA application in rice reduced Pb contents in shoot, leaves, panicle, and grains compared with Pb exposed plants without GABA. Overall, GXZ performed better than NX-18 under Pb toxic conditions.